ONLINE LEARNING CHALLENGES DURING PANDEMIC COVID-19: TEACHERS’ PERSPECTIVES - Rashed, Zetty Nurzuliana; Mohd Hanipah, Rahimah; Mohd Zhaffar, Nursafra (Journal of Islamic Educational Research, 2021)
Online learning (e-learning) has become something that is no stranger to us since the Covid-19 epidemic hit the world. This has caused teachers and students to drastically need to change the method of learning and facilitation (PDPC) by doing it online. There are some challenges faced by teachers living in rural areas especially facing the problem of teaching in cyberspace due to poor internet access. This study uses a qualitative approach by interviewing three secondary school Islamic Education teachers as study participants. The findings of the study found that teachers utilize social media such as WhatsApp and Telegram to convey various information, instructions, and training. Learning mediums also vary, from the Zoom app to Google Meet and video calls. In addition to online learning that is not ’real time’ such as using Google Classroom. Teachers also practice flexible online teaching and learning timetables according to the level of students to overcome the issue of parents who have problems with lack of gadgets but have many school children. With this flexible timetable, kids can use gadgets not simultaneously. As well as continuing challenges of Internet accessibility and facilities among students to participate in e-learning. Educators need to diversify online teaching and learning methods in line with the concept of 21st Century Learning (PAK21). The use of these appropriate and creative platforms is expected to be able to attract students to follow the learning sessions and to avoid dropouts.